The impact of morally injurious events in a refugee sample: A quantitative and qualitative study - Mooren, Nora; Boelen, Paul A.; de la Rie, Simone M. (Frontiers in Psychiatry, 2022)
Posttraumatic Stress Disorder (PTSD) is often reported by refugees that faced violence and persecution. Some stressful events also entail moral conflicts or dilemmas, described as “morally injurious events” (MIE). Very few studies have yet investigated the nature of these MIEs in traumatized refugees, using both quantitative and qualitative data. In this study, traumatic events of 183 patients were examined. Based on established definitions of a MIE, participants were allocated to a Moral Injury (MI) group if they reported lasting distress after exposure to an event of which the patient indicated that it transgressed his or her moral beliefs. The remaining participants were allocated to the No-MI group. The type of MIEs was categorized using qualitative analysis. The groups were compared in terms of PTSD severity, feelings of guilt, and general mental health symptoms. Of the total sample, 55 participants reported one or more acts of transgression (MI group) and 128 reported no acts of transgression (No-MI group). Analyses of MIEs elicited six themes 1) failing to prevent harm to others, 2) not giving aid to people in need, 3) leaving family members behind, 4) making indirect and direct moral decisions leading to injury or death of others, 5) betrayal, and 6) engaging in the harm of others. No differences were found between groups on the clinical outcomes, except for feelings of guilt. A considerable number of traumatized refugees reported confrontation with MIEs and experiencing MIEs appeared unrelated to elevated posttraumatic mental health issues.